Sound Intensity Distribution Around Organ Pipe - ODYA, Piotr; KOTUS, Józef; SZCZODRAK, Maciej; KOSTEK, Bożena (Archives of Acoustics, 2017)
The aim of the paper was to compare acoustic field around the open and stopped organ pipes. The wooden organ pipe was located in the anechoic chamber and activated with a constant air flow, produced by an external air-compressor. Thus, a long-term steady state response was possible to obtain. Multi-channel acoustic vector sensor was used to measure the sound intensity distribution of radiated acoustic energy. Measurements have been carried out on a defined fixed grid of points. A specialized Cartesian robot allowed for a precise positioning of the acoustic probe. The resulted data were processed in order to obtain and visualize the sound intensity distribution around the pipe, taking into account the type of the organ pipe, frequency of the generated sound, the sound pressure level and the direction of acoustic energy propagation. For the open pipe, an additional sound source was identified at the top of the pipe. In this case, the streamlines in front of the pipe are propagated horizontally and in a greater distance than in a case of the stopped pipe, moreover they are directed downwards. For the stopped pipe, the streamlines of the acoustic flow were directed upwards. The results for both pipe types were compared and discussed in the paper.